(untitled) (Numerus academy review, 2026)
This paper aims to shed light on the religious side of the American poetess Emily Dickinson; not as a typical Christian believer but a knowledgeable female intellectual towards Islam. Through Philosophical and Religious Approach, we are going to detect certain Quranic teachings such as Belief in only One Divine, Angles, Holy Books, Messengers, Last Day, and Destiny in a good deal of her work. Despite the fact that the Bible had been the basic relevance for her Christian conservative community, she attempted to widen and differentiate her culture religiously as well as stylistically. So, this paper provides an overview of Dickinson’s creative writings based on literary-critical responses combined with some relevant selected poems so as to assert the relevance of her work into Islam.